Directed trust and trustworthiness in a social network : an experimental investigation - Riyanto, Yohanes Eko (2019)
Trust and trustworthiness are important in social relationships. Levels of trust and trustworthiness are likely to depend on “social” utility; the magnitude of which is influenced by the social context governing individual relationships. Social networks are an example of such a social context. This paper investigates how social networks influence trust and trustworthiness by blending social network analysis with experimental economics methodology in two separate experiments. We show that trust and trustworthiness are higher for individuals who are more closely connected; in both cases, this relationship tapers off beyond second degree friendships. We also find that people tend to trust more central (popular) individuals. However, being more central (popular) has little influence on one's levels of trust and trustworthiness. We find these effects on trust to be only partially driven by the expectation of trustworthiness. We thus document evidence of a bias toward more closely connected and more popular individuals.